Digital connection and disconnection: a reflection - Ortoll, Eva; Cobarsí-Morales, Josep (Anuario ThinkEPI, 2016)
An analysis of how people use information and communication technology under the metaphor of Digital Visitors and Residents, the results of which show the use of technologies, the Internet, and social networks depends heavily on the situation and context. This article also reflects on the effects of technological stress, infoxication, and the different ways people self-regulate their technological behavior.
Keywords: Digital infoxication; Digital literacy; User behavior